A Novel Coil With High Misalignment Tolerance for Wireless Power Transfer - Li, Yang; Zhao, Jingtai; Yang, Qingxin; Liu, Liu; Ma, Jingnan; Zhang, Xian (IEEE transactions on magnetics, 2019)
Aiming at the problem of decrease in efficiency due to misalignment of wireless power transfer (WPT) coil, a novel coil with high misalignment tolerance was proposed. First, the factors that affect the efficiency and the method of improving the efficiency and misalignment tolerance of the coil are analyzed. Second, the novel coil was set up through COMSOL simulation, which was compared with double-D (DD) coil and circular coil in misalignment tolerance. Finally, in order to verify the authenticity of theory and simulation, experiment device is implemented and experimental results show that the coupling coefficient changes affect coil efficiency, and the flat and high magnetic flux density can better maintain coil efficiency when lateral misalignment happened. This means that the novel coil has better misalignment tolerance, which can meet the demands of WPT system.